Implementasi Media Tv Sekolah dalam Meningkatkan Minat Belajar Anak Usia Dini Kelompok B di RA Amal Shaleh Jember - Sofiyatul Anshoriyah; Sri Watini (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2022)
This research is motivated by the lack of interest in early childhood in learning. This can be seen that there are still many early childhood children who are busy with themselves because during the learning process the teacher is only verbalistic without using the media. So that children do not understand what is explained by the teacher. The aim of this research is to prove whether school TV media can increase interest in early childhood learning. This study uses a qualitative method with a case study type. This study aims to describe the implementation of school TV in increasing reading interest in early childhood. The results of this study are that school TV is able to increase interest in early childhood learning at school or at home. With the school stage created by the RA Amal Salih institution, the children are enthusiastic about learning. With school TV media, it can also reduce early childhood playing online games, which so far by playing online games, early childhood learning interest has decreased.